Speleothem magnetism: environmental and geomagnetic records from Brazil - Jaqueto, Plinio Francisco (2021)
In the last decade, a revival in the use of stalagmites for paleomagnetic and environmental magnetism was observed. The advent of more sensitive magnetometers and a new generation of radiometric dating techniques made it possible to obtain high-resolution magnetic records in speleothems. In this thesis, both aspects of speleothem magnetism research were explored. First, a database of magnetic mineral properties from 22 caves in Brazil was built to comprehend the magnetic signal recorded in tropical-subtropical karst regions and how it relates to biomes and climate at different latitudes. This database has demonstrated the pervasive occur-rence of low-coercivity magnetic minerals, without significant changes in magnetic mineral-ogy across the studied speleothem, all presenting pedogenic magnetite/maghemite (and sometimes goethite). Its concentration parameters presented some correlation with the local biome. These results reinforce the hypothesis that the soil\'s local dynamics above the cave control the magnetic signal recorded in speleothems. Then, two high-resolution records of the geomag-netic field were obtained from sites in western Brazil under the influence of the South Atlantic Anomaly. In this region, the geomagnetic field presents the lowest intensity value of the globe. Both sites provided coherent directional and relative paleointensity results. The last two millennia were investigated with two stalagmites from Pau dAlho cave (15.21° S, 56.81° W) and revealed fast angular variations (> 0.10°/yr) for two distinct periods at 860 CE to 960 CE and 1450 CE to 1750 CE. These variations correspond to records obtained in South Africa with a westward time lag of ~200 years and express the recurrence of the South Atlantic Anomaly in the last two millennials in the southern hemisphere. This behavior is explained by the westward drift of reverse flux patches at the core-mantle boundary accompanied by their intensification and expansion. A stalagmite from Dona Benedita cave (20.57° S, 56.72° W) encompasses ~2100 years of record from mid-to-late Holocene. In contrast to the Pau d\'Alho speleothems, the Dona Benedita speleothem revealed low angular variations below 0.06°/yr, expressing a low activity of non-dipolar sources in South America for this period, ultimately revealing that the South Atlantic Anomaly is an intermittent or absent feature whose expression depends on the non-dipole/dipole ratio of geomagnetic components and the density of re-verse flux patches in the southern hemisphere. Therefore, the magnetic record of speleothems provided key information for the reconstruction of soil dynamics and for tracking at high-resolution the evolution of the geomagnetic field in South America, where data is known to be scarce.